(untitled) (EAAE Annual Conference Proceedings, 2019)
For one and a half year, we have been renting the 24th floor of the abandoned WTC1-building, a tower waiting for total restructuring financed by a Regulated Real-estate Investment Trust (BE-REIT), listed on Euronext Brussels. 1500 m² of free space. This floor is located next to the north station, which connects people between the big city and smaller ones. The North Station connects trains with trams and buses. The North Station connects fast food with a bike point. The North Station is, or was a building. Not anymore. Today, it does not imply connection, only separation, brutal transition, inhospitability, emptiness, refreshed decay.